A implementação da estratégia nacional de defesa, 2008-2013 - Barcelos, Marco Antonio dos Santos (2014)
The debate on defense in Brazil still remains far short of its strategical importance for the country. However, in recent years, the question got more importance and issues related to this subject began to gain more prominence, including in the media (for example, the military Gripen fighter aircraft purchase). The institutionalization of defense in Brazil had important milestones since the creation of the Ministry of Defense (MD) in 1999, through the elaboration of National Defense Policy (PND) in 2005, the National Defense Strategy (END) in 2008 and, finally, National Defense White Paper (LBDN) in 2012. Civil-military relations are grounded by visions often distinct about defense, but greater convergence is needed in achieving shared understanding. However, there is still a long way to be traversed until the society is able to understand and gets more involved with such relevant topic of national interest. The purpose of this study is to analyze the degree of implementation of the National Defense Strategy policies and to evaluate the factors that influenced the actions that were proposed for its execution.